Towards comfortable communication in future vehicles. (July 2019) - Piro, Silvana; Fiorillo, Iolanda; Anjani, Shabila; Smulders, Maxim; Naddeo, Alessandro; Vink, Peter
Abstract: This research aims to study the effect of seat and/or backrest rotation on comfort and quality of conversation. Different sitting arrangements were tested to study the effect of the seat layout on: 1) (dis)comfort experience; 2) conversation quality and 3) postures. Two seats were arranged in different angles (0°, 45°, 90°, and 180°) at the same distance (1 m) and participants were asked to talk to each other. The participants' postures were acquired by using cameras and markers on the participants' body. Questionnaires were used to rate the perceived (dis)comfort and quality of conversation. Results show that 90° configuration scored the best both in overall comfort and quality of conversation; while the 0° configuration scored the lowest in both ratings. A strong correlation was established between high comfort and good quality of conversation. Highlights: Effects of sitting arrangements on comfort and conversation quality have been studied. 0°, 45°, 90°, 180° configurations have been investigated at the same distance. 90° is the best configuration for both perceived comfort and conversation quality. The participant felt restricted in the social interaction in the 0° configuration. There is a strong correlation between high comfort and good conversation quality.